2011
DOI: 10.1530/rep-10-0358
|View full text |Cite
|
Sign up to set email alerts
|

Microarray assessment of the influence of the conceptus on gene expression in the mouse uterus during decidualization

Abstract: During pregnancy in several species including humans and rodents the endometrium undergoes decidualization. This process of differentiation from endometrial to decidual tissue occurs only after the onset of implantation in mice. It can also be artificially-induced causing the formation of deciduomal tissue. The purpose of this study was to compare the gene expression profile of the developing decidua in pregnant mice with the deciduoma formed after artificial induction in an effort to identify conceptus-influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 81 publications
1
45
0
Order By: Relevance
“…5A). Previously, we found uNK cell numbers are significantly decreased in uteri undergoing bead-induced decidualization by days 7.5 and 8.5 (Herington & Bany 2007b) but in a recent microarray study, differences in Avil mRNA levels were not seen between the decidua and deciduoma on Day 7.5 (McConaha et al 2011). Therefore, we examined Avil mRNA levels in IS tissue of pregnant mice and bead-induced deciduomas (BID) of pseudopregnant mice on days 4.5–8.5.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…5A). Previously, we found uNK cell numbers are significantly decreased in uteri undergoing bead-induced decidualization by days 7.5 and 8.5 (Herington & Bany 2007b) but in a recent microarray study, differences in Avil mRNA levels were not seen between the decidua and deciduoma on Day 7.5 (McConaha et al 2011). Therefore, we examined Avil mRNA levels in IS tissue of pregnant mice and bead-induced deciduomas (BID) of pseudopregnant mice on days 4.5–8.5.…”
Section: Resultsmentioning
confidence: 67%
“…The expression of several genes such as Vegfa (Halder et al 2000), Ptgs2 (Lim et al 1997, Matsumoto et al 2002), Gja1 (Laws et al 2008), Angpt2 (Matsumoto et al 2002, Hess et al 2006), Tie2 (Matsumoto et al 2002), Flt1, Kdr (Chakraborty et al 1995, Douglas et al 2009) are believed to play a role in angiogenesis in the endometrium during decidualization. Further, several endothelial vascular endothelial cell markers such as Flt4 (Douglas et al 2009), Cd34 (Morison et al 2007), Pecam1 (Ma et al 1997), Adamts9 (Jungers et al 2005) and Inhbb (McConaha et al 2011) have been shown to be expressed in the endometrial endothelial cells during decidualization. Notably, with the exception of Adamts9 which is an anti-angiogenic factor, none of the other genes were differentially expressed in IS tissues between Il15 +/+ and Il15 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial deciduomas are masses of decidual tissue that form when an artificial stimulus, such as needle scratching or oil, is applied to the endometrium in a hormonally primed female (30). Importantly, deciduomas display biochemical, architectural, and immunological properties similar to those of true deciduas induced by the implantation of blastocysts (31,32). We used a common approach to generate deciduomas, namely, mating female mice with vasectomized males, followed 3 days later (day 3.5 postcopulation [DPC3.5]) by intrauterine injection of sesame oil.…”
Section: Resultsmentioning
confidence: 99%
“…The disappearance of primary decidual zone which forms a barrier surrounding the embryo and reduced immune cell population in deciduoma further emphasize the importance of embryo-uterus dialogue (Herington and Bany, 2007b; Wang et al, 2004d). Using microarray approaches, the differentially expressed genes responsive to (Bany and Cross, 2006; Herington and Bany, 2007a; Herington and Bany, 2007b, 2009; Herington et al, 2009; Kashiwagi et al, 2007; McConaha et al, 2011)the living embryo versus artificial stimuli further prove the paracrine signals from the embryo regulating the decidua development (Bany and Cross, 2006; Herington and Bany, 2007a; Herington and Bany, 2007b, 2009; Herington et al, 2009; Kashiwagi et al, 2007; McConaha et al, 2011). Collectively, these findings highlight the necessity of embryo-derived signals for normal implantation and decidualization.…”
Section: Embryonic Preparation For Implantation Necessitates “Blasmentioning
confidence: 97%